ANALYSIS OF EMPLOYEE PERFORMANCE ON PROTOCOL AND COMMUNICATION OF THE HEAD OF THE REGIONAL SECRETARIAT OF KLATEN REGENCY - Nugroho, Tri; Sudarwati, Sudarwati; Istiatin, Istiatin (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
Research was conducted to determine the influence of leadership, motivation, competence, and work environment on employee performance. With the census method, a sample of 38 respondents was obtained and the data analysis used was a classical assumption test, multiple linear regression test, hypothesis test and determination coefficient test. The research variables consist of dependent variables, namely employee performance, independent variables, namely leadership, motivation, competence, and work environment. The population in this study was 38 respondents. Based on the results of hypothesis testing and discussions that have been carried out, it can be concluded that there is an influence of leadership, motivation, competence, and work environment on employee performance in Prokopim Klaten Regency. Based on the research and discussion conducted, the results of the Adjusted R Square (R²) value of 0.818 or 81.8% were obtained. The remaining contribution of other variables only amounted to 18.2% such as work ethic, work discipline, education and others.